Individuals post Achilles tendon rupture exhibit asymmetrical knee and ankle kinetics and loading rates during a drop countermovement jump - Powell, H. C.; Grävare Silbernagel, K.; Brorsson, A.; Tranberg, R.; Willy, R. W. (Journal of Orthopaedic & Sports Physical Therapy, 2018)
Asymmetrical knee loading during jogging and hopping has been reported in individuals who have ruptured their Achilles tendon. No studies have examined knee loads in individuals post Achilles tendon rupture during high-demand tasks, such as single-limb landings. Objectives: We sought to determine whether individuals post Achilles tendon rupture demonstrated asymmetrical knee loads and impact forces during drop countermovement jumps (CMJs). Methods: Achilles tendon length and the single-leg heel-rise test for endurance were assessed in 34 individuals (31 male) 6.1 ± 2.0 years post Achilles tendon rupture. Movement patterns were assessed during a drop CMJ. Data were analyzed via repeated-measures analyses of variance, with comparisons between limbs and prior treatment history (surgery versus nonsurgery). Results: An 8.6% longer Achilles tendon (P<.001) was found in the involved limb. During the single-leg heel-rise test, the involved limb demonstrated 22.4% less endurance and 14.6% lower heel-rise height (all, P<.001). During the landing phase of the drop CMJ, the involved limb exhibited 39.6% greater loading rate (P<.001), 16.8% greater eccentric knee power (P = .048), but 21.6% lower eccentric ankle power (P<.001). During the take-off phase, the involved limb exhibited 12.1% lower jump height and 19.9% lower concentric ankle power (both, P<.001). Conclusion: Elevated eccentric knee joint power and higher loading rates during a drop CMJ in individuals who experienced Achilles tendon rupture several years earlier may be a compensation pattern for reduced plantar flexor function. This movement pattern may place individuals who have had an Achilles tendon rupture at greater risk for knee injuries.